ANALISIS KUALITATIF KANDUNGAN SAKARIDA DALAM TEPUNG DAN PATI UMBI GANYONG (Canna edulis Ker.) - Kusbandari, Aprilia (Universitas Ahmad Dahlan, 2015)
Canna Tubers (Canna edulis Ker.) is one of the plants producing carbohydrates. ItsÂ also contains of protein, fat, vitamins, minerals,Â phosphorus, iron and more calciums. The purpose ofÂ this study is to identify ofÂ sugarÂ in the powder and starch from canna tuber is a hydrolysis and didnât hydrolysis. The method of qualitative analysis with tube testÂ andÂ Thin Layer Chromatography (TLC). The result indicated that before hydrolysisÂ canna powderÂ gaveÂ sucrose (Rf = 0.45) and mannose (Rf=0.51), while after hydrolysis it gaveÂ glucose (Rf=0.44), fructose (Rf=0.61) and mannose (Rf=0.51). In addition, canna starch gaveÂ Â glucose (Rf=0.44) and maltose (Rf=0.35).